Pathology and Characterization of Fowlpox Virus Infection in a Turkey-Chicken Backyard Flock, Nigeria - Akanbi, Olatunde Babatunde (Universitas Airlangga, 2022)
Cutaneous scabs were seen on the nares and shanks in three grower turkeys in a mixed turkey-chicken flock in Langtang-north LGA of Plateau State, Nigeria. A chicken in the flock had diphtheritic membrane covering the mucous membranes of the oro-pharynx and the turkeys had cutaneous pox lesions on the nares and shank. Fowlpox virus infection was diagnosed by gross and histopathology and confirmed by isolation of the virus in chorioallantoic membrane of 9-12 weeks chicken embryonating eggs. The DNA of Fowl Pox Virus (FPV) was detected in the cutaneous scabs of the turkey and chicken using Polymerase Chain Reaction (PCR) which amplified a 578 base pairs fragment of the 4b core protein gene. Sequencing and phylogenetic analysis revealed that the fowlpox virus responsible for this infection clustered with the sublineage A1 genotype of clade A of fowlpox virus and shares 98% homology with the vaccine strain produced in Nigeria. The sequence has been deposited in the GenBank under the accession number MK435242. Our results confirmed the presence of FPV in the turkeys and suggest a predisposition by the chickens. We therefore suggest vaccination for small holder poultry to mitigate against mortality in turkeys and chickens and molecular epidemiology of fowlpox viruses in Nigeria to unravel viral evolution.